Caring for the dying: guidelines and perspectives - Petrini, Massimo (Medicina e Morale, 2024)
The subject of death is today enjoying a reawakening of interest on the part of a society that believes, in some areas, that it has worked out a humane answer to this problem, which is what euthanasia wants to be. It is almost a stoic gasp of a culture that wants to affirm that human life contains within itself its own exhaustive meaning; a gasp of a culture that, wanting to forget Revelation, is no longer capable of realising a right attitude in the face of birth and dying.